Galvanic replacement reaction for in situ fabrication of litchi-shaped heterogeneous liquid metal-Au nano-composite for radio-photothermal cancer therapy - Zhenhu Guo; Jingsong Lu; Dan Wang; Wensheng Xie; Yongjie Chi; Jianzhong Xu; Nonaka Takuya; Junxin Zhang; Wanling Xu; Fei Gao; Hong Wu; Lingyun Zhao (Bioactive Materials, 2021)
With tremendous research advances in biomedical application, liquid metals (LM) also offer fantastic chemistry for synthesis of novel nano-composites. Herein, as a pioneering trial, litchi-shaped heterogeneous eutectic gallium indium-Au nanoparticles (EGaIn-Au NPs), served as effective radiosensitizer and photothermal agent for radio-photothermal cancer therapy, have been successfully prepared using in situ interfacial galvanic replacement reaction. The enhanced photothermal conversion efficiency and boosted radio-sensitization effect could be achieved with the reduction of Au nanodots onto the eutectic gallium indium (EGaIn) NPs surface. Most importantly, the growth of tumor could be effectively inhibited under the combined radio-photothermal therapy mediated by EGaIn-Au NPs. Inspired by this approach, in situ interfacial galvanic replacement reaction may open a novel strategy to fabricate LM-based nano-composite with advanced multi-functionalities.